The Rational Reconstruction of the History of Science: A Problem or A Pseudoproblem? - Jankauskas, Skirmantas (Problemos, 1984)
In the middle of sixties a heated discussion concerning rationality of science has arisen in the postpositivist philosophy. T. Kuhn in his book “The Structure of Scientific Revolutions” while studying science has supplemented a logical analysis of the history of science with a socio-psychological one. The followers of K. Popper, and in the first place I. Lakatos, considered this to be a totally unjustified resignation to irrationalism. They tried to demonstrate the possibility of the exceptionally logical and to their minds rational reconstruction of the history of science. In the article an attempt is made to retrace the historical origins of the controversy.